Peran Orang Tua dalam Mencegah Paparan Asap Rokok pada Anak Usia Dini - Farhan Julianto (Universitas Maritim AMNI Semarang, 2025)
Children as the next generation of the nation require special attention to health aspects to ensure optimal growth and development. One of the worrying health threats is the high exposure of children to cigarette smoke, which contains dangerous chemicals such as nicotine, tar, and carbon monoxide. Exposure to cigarette smoke can damage the respiratory system, interfere with brain development, and affect the function of vital organs, especially in early childhood whose body systems are still vulnerable. The impacts include an increased risk of respiratory tract infections, asthma, and various other health problems that can have long-term impacts. The role of parents is very important in efforts to prevent exposure to cigarette smoke, starting from setting an example by not smoking to creating an environment free from cigarette smoke. In addition, education about the dangers of cigarette smoke needs to be given to children from an early age to increase their awareness of the importance of maintaining health. The active role of parents in building a healthy environment and educating children about the risks of cigarette smoke is an essential step in creating a healthier generation free from exposure to cigarette smoke.